Effect of incubation and liming on the phosphorus fractions in soil - Kaila, Armi (Agricultural and Food Science, 1961)
Samples from two field trials were incubated at 20°C for seven months with or without an addition of 1 per cent CaCO3. Both the samples of loam soil and silt soil originated from the surface inch of plots treated with no phosphate, superphosphate or hyperphosphate, resp. It was found that liming did not in any case increase the amount of organic phosphorus mineralized during the incubation. Its effect was observed in the distribution of this phosphorus in the various fractions of inorganic phosphorus. In the distinctly acid samples which were incubated without lime the mineralized phosphorus seemed to accumulate as the ammonium fluoride-soluble and alkali-soluble forms, while in the neutral samples incubated with lime an increase only in the former fraction was detected. When the samples from the hyperphosphate plots were incubated without lime, apparently some apatite of the fertilizer was dissolved and sorbed as the ammonium fluoride soluble or alkali-soluble forms. No decrease in the acid-soluble fraction of these samples incubated with lime did occur.